Analysis of the Influence of Parental Education Level and Learning Discipline on Student Learning Achievement - Moslimah, Moslimah (International Journal of Business, Law, and Education, 2025)
This research aims to analyze the influence of parental education level and learning discipline on student learning achievement. This research used a quantitative approach with a population of all class VI students at Madrasah Ibtidaiyah Raudhatul Ulum Pematang Rambai, totaling 45 students. The sampling technique used the total population, consisting of 24 students in class VI-A and 21 students in class VI-B. Data collection was carried out using the questionnaire method, while data analysis used the SPSS version 25 program for Windows. The results of the regression analysis show an R Square value of 0.516, which indicates that the variables of parental education level (X1) and student learning discipline (X2) contribute 51.6% to student learning achievement (Y). The effective contribution of variable X1 is 2.77%, while X2 is 48.83%. Thus, it can be concluded that the level of parental education and student learning discipline have a positive influence on increasing the learning achievement of class VI students at Madrasah Ibtidaiyah Raudhatul Ulum Pematang Rambai